I. Lewis minimally invasive esophagectomy - G. Yu. Savenko; O. Ye. Sydiuk (Zaporožskij Medicinskij Žurnal)
The aim of the study was to improve the direct results of surgical treatment for esophageal diseases by implementing the method of minimally invasive esophagectomy according to I. Lewis.